PEMBERITAAN PERTANIAN OLEH SURAT KABAR DAERAH: - STUDI KASUS PADA RUBRIK KANDA RAHARJA SKH. KEDAULATAN RAKYAT - - Ngatif, Muh. Syaiful; Harsoyo, Harsoyo; Subejo, Subejo (Jurnal Ilmu-Ilmu Pertanian, 2005)
The Study aims to know and to analyze the comparison between agricultural news and non-agricultural news in term off frequency, space, length, position, topic and coverage area on special rubric of agricultural issues of Kedaulatan Rakyat daily newspaper. Another purpose of the study was to know about editorial policy of the newspaper in reporting agricultural news and information. The research method used in the study was "descriptive method" by applying of "content analysis" technique. Data of 16 publications during May-December 2004 were used in the study. Main findings of the study were: (1) total number of space and length of agricultural news were larger as compared to non-agricultural news, (2) position of agricultural news in the top of the paper were larger as compared to non-agricultural news, (3) agricultural news from non-governmental sources were larger as compared to governmental sources, (4) news topics of agricultural production and forestry and miscellaneous were dominant, (5) coverage area of local agricultural news were larger as compared to non-local news, (6) the editorial policy had some flexibilities in arranging and selecting of coverage area, they were not only on local issues, but also extended into large area or non-local news.